Financing Alignment and Financing Performance of Chinese Companies within Buyer-Supplier Relationships: The Moderate Effect of Supply Chain Finance Challenges - Ashfaq, Muhammad; Zhang, Aoer; Tariq, Adeel; Hasan, Rashedul (International Journal of Supply Chain Management, 2020)
Purpose – The aim of this study is twofold. In academia, this study attempts to enrich the scarce empirical literature regarding Supply Chain Finance (SCF) adoptions. In practice, this study aims to support the buyers and suppliers in a supply chain that consider the application of blockchain technology in SCF, especially in emerging countries.Design/ methodology/ approach – Through a cross-industry survey, 152 responses from companies located in China have been collected to test the hypotheses empirically.Findings – The results show that buyer-supplier financing alignment could positively influence on the buyer-supplier financing performance in the context of Chinese companies. However, insufficient evidence exists to suggest a moderating effect of SCF challenges.Research limitations/ implications – Future study may identify the related challenges within the blockchain technology-driven SCF. An additional in-depth case study might be a desirable methodology to realize how Chinese companies implement SCF, and gain insights that are more practical. Another possibility is to generalize the research model to other emerging countries. Further, future research may also consider involving other participants within the supply chain to investigate the SCF issues in China.Practical implications – This paper implies that both buyers and suppliers could consider applying blockchain technology-driven SCF to enhance the financial performance in a supply chain. Additionally, when companies are implementing SCF, it is essential to maintain the long-term buyer-supplier relationship in order to improve the financing performance. Originality/ value – This study enriches the scarce empirical researches regarding SCF adoptions. Meanwhile, this study tries to shed light on the influence of buyer-supplier financing alignment on buyer-supplier financing performance, especially in the emerging country.Keywords – Supply chain finance, Finance collaboration, Finance performance, Challenges, China